Reclamation and amelioration of saline-sodic soil using gypsum and halophytic grasses: Case of Golina-Addisalem irrigation scheme, Raya Kobo Valley, Ethiopia - Sisay Abate (Cogent Food & Agriculture, 2021)
In Golina-Adisalem irrigation scheme, 500 ha becoming salt-affected. Rehabilitation of salt-affected fields using drainage is expensive and leaching by far not feasible in shallow water table areas. The alternative way is chemical amendment and bioremediation. Therefore, the field experiment was conducted to evaluate the possibility of using gypsum soil amendment and halophytic grasses on modification properties of saline-sodic soil, and their effects on infiltration. The gypsum levels (0%, 75%, 100%, 125% gypsum requirement) and halophytic grasses (Chlorosis Guayana and Cynodon Dactaylon) were set in factorial RCBD design with three replications. After the 2nd harvest, the highly significantly (P < 0.01) lowest pHe (7.23, 7.29, 7.51), ECe (4.62, 4.89, 4.31 dS m−1), SAR (10.78, 15.81, 16.38), and ESP (8.93, 8.66, 9.47%) were recorded from Chlorosis Guayana+125% gypsum requirement (G) and Cynodon Dactaylon +125% gypsum requirement (G) applied treatment, whereas the highest pHe (8.54, 8.66, 8.77), ECe (20.1, 16.31, 11.431dS m−1), SAR (50.12, 54.23, 57.29) and ESP (57.37, 66.22, 72.26%) was obtained from the control treatment for 0–20, 20–40, 40–60 cm depths, respectively. The reclamation efficiency of Chlorosis Guayana+125% G was statistically equal with Cynodon Dactaylon +125% G. The highest infiltration rates were noted from soils treated with Chlorosis Guayana+125% G (6.3 cm/hr) and Cynodon Dactaylon+125% G (5.92 cm/hr); while the lowest value (1.22 cm/hr) was recorded from the control treatment. Therefore, the combined application of Chlorosis Guayana (Rhodes grass massava variety)+125% G and Cynodon Dactaylon (Panicum grass maxima variety)+125% G was the most efficient treatment for improving saline-sodic soil.